Efficacy of Autologous Serum Therapy in patients with Chronic Urticaria - ونوس بشرى; محمد عادل اسماعيل; جمال خدام (Latakia University Journal -Medical Sciences Series, 2022)
Objective: To evaluate the efficacy of Autologous Serum Therapy (AST) in patients with Chronic Urticaria and compare the efficacy of AST in both Autologous Serum Skin Test (ASST) positive and negative groups. Settings and design: A prospective study (before & after). Methods and materials: We enrolled 50 patients suffering from Chronic Urticaria. ASST was done in all patients. Autologous serum was given intramuscularly weekly for 9 weeks. The effect of AST was evaluated by using Urticaria Total Severity Score (UTSS) at baseline (0 weeks), at the end of the treatment (9 weeks), and followed up for 3 months after the end of the treatment (21 weeks). Results: Among 50 patients, ASST was positive in 25 patients (50%) and negative in 25 patients (50%). 18 patients (36%) had an excellent improvement, 7 patients (14%) had a very good improvement, 11 patients (22%) had a good improvement, and 14 patients (28%) had no improvement. The treatment was effective in both ASST positive and negative groups, however there was no significant relationship in improvement between two groups. The patients with excellent improvement were in ASST (+) group (52%) more than ASST (-) group (20%), and it was statistically significant (p-value=0.02). There was a significant relationship between clinical improvement and severity of disease (p-value = 0.04), the majority of excellent improvement cases (88.9%) had severe disease before the treatment. Conclusion: AST was effective in the treatment of Chronic Urticaria with no side effects. The treatment was effective in both ASST (positive and negative) groups.